Do Import Tariffs Increase Domestic Production or Value in World Consumption? A Study of Global Value Chain Impicatons for Selected Sectors - Mukherjee, Deeparghya (Economic and Political Weekly, 2024)
Since 2014, India has been raising tariffs in various sectors. This paper explores the responsiveness of imports to tariff hikes for specific tariff lines and investigates the effect on production, value added and India$1 (Bs changing nature of participation in global value chains. We find that while production and value added by India have increased for all sectors, the share of production exported has decreased. Analysing the results, we conclude with possible policy directions for India in light of current geopolitical developments and trade agreements being negotiated.s
Keywords: Domestic Production; Global Value Chain; World Consumption; Import Tariffs